Structure and activity of strontium substituted LaCoO3 perovskite catalysts for syngas conversion - Ao, M.; Pham, Gia; Sage, V.; Pareek, Vishnu (Elsevier Science, 2016)
© 2016 Elsevier B.V. All rights reserved. Study of the catalytic activity of LaCoO3 perovskite catalysts with varying degrees of strontium substitution (La1-xSrxCoO3) in the Fischer-Tropsch synthesis is presented for the first time in this paper. It was found that Sr substitution improves the catalyst's reducibility and increasing strontium substitution beyond a threshold of 10 mol% Sr has an inverse effect on the catalytic performance in the syngas conversion. For x = 0.1, the catalysts exhibited a stable rhombohedral structure, which leads to well dispersion of active centre Co0 during the reduction process and displayed a high catalytic activity. For x = 0.2 the catalyst structure was gradually changed, from a rhombohedral to a less stable cubic structure, and leads to Co0 sintering. The turnover frequency of Co atom in the Fischer-Tropsch reaction decreased significantly with increasing strontium substitution levels due to the loss of active catalyst surface. The La0.9Sr0.1CoO3 catalyst showed the highest catalytic activity in the Fischer-Tropsch synthesis.